Evaluation of In Vitro Anti-inflammatory Activity of Azomethines of Aryl Oxazoles. (2011) - Niraimathi, V.; Suresh, A. Jerad; Latha, T.
Abstract : Ability to inhibit erythrocyte hemolysis is often used as a characteristic of the membrane stabilising action of chemical compounds. Azomethines of aryl oxazoles were evaluated for anti-inflammatory by in vitro hemolytic membrane stabilising study. The effect of inflammation condition was studied on erythrocyte exposed to hypotonic solution. In this in vitro method the membrane stabilising action leads to anti-inflammatory activity and was compared with that produced by diclofenac sodium as the reference standard. Results of the evaluation indicate that the synthesised compounds found to exhibit membrane stabilising activity.